Behavioral and distributional effects of environmental policy - Carraro, Carlo; Metcalf, Gilbert E. (National Bureau of Economic Research conference report., 2001)
Most people would agree that it makes sense to tax a company that pollutes in a way that directly reflects the amount of environmental and social damage it has done. Yet in practice, such taxes are fraught with difficulty and have far-reaching implications. A company facing a new tax may lay off workers, for example, exacerbating an unemployment problem. This volume focuses on such external issues and examines in detail the trade-offs involved in designing policies to deal with environmental problems. Reflecting the broad nature of the subject, the contributors include leading economists in th.